Evaluation of the foetal time to death in mice after application of direct and indirect euthanasia methods. (April 2016) - Muñoz-Mediavilla, C; Cámara, J A; Salazar, S; Segui, B; Sanguino, D; Mulero, F; de la Cueva, E; Blanco, I
Directive 2010/63/EU on the protection of animals used for scientific purposes requires that the killing of mammal foetuses during the last third of their gestational period should be accomplished through effective and humane methods. The fact that murine foetuses are resistant to hypoxia-mediated euthanasia renders the current euthanasia methods ineffective or humane for the foetuses when these methods are applied to pregnant female mice. We have assessed the time to death of foetuses after performing either indirect (dam euthanasia) or direct (via intraplacental injection – a new approach to euthanasia) euthanasia methods in order to determine a euthanasia method that is appropriate, ethical and efficient for the killing of mouse foetuses. The respective times to death of foetuses after performing the three most commonly used euthanasia methods (namely cervical dislocation, CO2 inhalation and intraperitoneal sodium pentobarbital administration) were recorded. Absence of foetal heartbeat was monitored via ultrasound. We consider that the most effective and humane method of foetal euthanasia was the one able to achieve foetal death within the shortest possible period of time. Among the indirect euthanasia methods assessed, the administration of a sodium pentobarbital overdose to pregnant female mice was found to be the fastest for foetuses, with an average post-treatment foetal death of approximately 29.8 min. As for the direct euthanasia method assessed, foetal time to death after intraplacental injection of sodium pentobarbital was approximately 14 min. Significant differences among the different mouse strains employed were found. Based on the results obtained in our study, we consider that the administration of a sodium pentobarbital overdose by intraplacental injection to be an effective euthanasia method for murine foetuses.